2019
DOI: 10.17844/jphpi.v22i2.28832
|View full text |Cite
|
Sign up to set email alerts
|

The Difference Characteristicsof Collagen from Tilapia (Oreochromis niloticus) Bone, Skin, and Scales

Abstract: Tilapia (Oreochromis niloticus) is one of the main commodities of freshwater fish in Indonesia. Mostly, tilapia is exported in the form of fillets which produce residual processing including bobe, skin, and scales which can reach 50 to 70% of the total weight of fish. The aimed of this study was to extract and characterize collagen from bone, skin, and scales of tilapia. The research method used a Completely Randomized Design (CRD) by treating the different types of collagen raw materials, namely bone, skin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 12 publications
1
6
0
8
Order By: Relevance
“…Based on research [19] in the preparation of skin moisturizing gel, the higher the addition of collagen concentration which is formulated to give a yellowish color. This is in accordance with the opinion of [14] collagen from tilapia scales has a low brightness. Tilapia fish scale collagen has a yellowish white color and low brightness.…”
Section: Colorsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on research [19] in the preparation of skin moisturizing gel, the higher the addition of collagen concentration which is formulated to give a yellowish color. This is in accordance with the opinion of [14] collagen from tilapia scales has a low brightness. Tilapia fish scale collagen has a yellowish white color and low brightness.…”
Section: Colorsupporting
confidence: 92%
“…This corresponds to [13] showed that the addition of collagen with different concentrations had a significant effect on the pH value of water-based ointments. The decrease in the pH value of the ointment is thought to be due to the process of making collagen using an acid solution (CH3COOH) so that it produces collagen which tends to be acidic [14]. The higher the concentration of collagen addition, the lower the pH level of the ointment.…”
Section: Ph Ointmentmentioning
confidence: 99%
“…Based on Romadhon's research [2], collagen in tilapia fish bones has a pH value that is not much different from the research of Sembiring et al [24]. These results are lower than the collagen quality requirements of SNI 8076: 2014, namely 6.5 -8, but slightly higher than the collagen pH of several collagen brands for cosmetics reported by Peng et al [25], which ranges from 3.8 to 4.7.…”
Section: Collagen Phmentioning
confidence: 71%
“…Collagen morphology can be displayed using Scanning Electron Microscopy (SEM). Based on Romadhon's research [2] using SEM with a magnification of 3000x, it can be seen that the collagen from tilapia fish bones is shaped like a sheet with a slight porous surface, while the collagen from the skin and scales of tilapia has the same morphology, which is in the form of small boxes and a smooth surface without pore. Arumugam et al [13] also conducted morphological observations with SEM at 500x magnification of fish collagen where collagen looks like fiber.…”
Section: Fish Bone Collagenmentioning
confidence: 99%
See 1 more Smart Citation